Optimizing Parallel I/O Accesses through Pattern-Directed and Layout-Aware Replication - He, Shuibing; Yin, Yanlong; Sun, Xian-He; Zhang, Xuechen; Li, Zongpeng (IEEE transactions on computers, 2020)
As the performance gap between processors and storage devices keeps increasing, I/O performance becomes a critical bottleneck of modern high-performance computing systems. In this paper, we propose a pattern-directed and layout-aware data replication design, named PDLA, to improve the performance of parallel I/O systems. PDLA includes an HDD-based scheme H-PDLA and an SSD-based scheme S-PDLA. For applications with relatively low I/O concurrency, H-PDLA identifies access patterns of applications and makes a reorganized data replica for each access pattern on HDD-based servers with an optimized data layout. Moreover, to accommodate applications with high I/O concurrency, S-PDLA replicates critical access patterns that can bring performance benefits on SSD-based servers or on HDD-based and SSD-based servers. We have implemented the proposed replication scheme under MPICH2 library on top of OrangeFS file system. Experimental results show that H-PDLA can significantly improve the original parallel I/O system performance and demonstrate the advantages of S-PDLA over H-PDLA.